KNOWLEDGE, ATTITUDE, AND PRACTICE OF COUGH ETIQUETTE IN PATIENTS WITH TUBERCULOSIS IN THE COMMUNITY HEALTH CENTERS - Yani, Desy Indra; Hidayat, Yayat Fajar; Amrullah, Afif Amir (Belitung Raya Foundation, Indonesia, 2018)
Background: Tuberculosis is the major global health problem. A high number of tuberculosis cases are as a result of the disease spreads through droplet nuclei which mainly through a cough. Transmission prevention of tuberculosis is important to lower the rate of new infection. Since the transmission is through a cough, therefore, one of the preventive behaviors is by implementing the good and right cough etiquette. Objectives: The aim of this study was to find out the overview of knowledge, attitude and practice of cough etiquette in patients with tuberculosis. Methods: This study was descriptive quantitative with the cross-sectional approach. The population were all patients with Acid-Fast Bacillus (AFB) and tuberculosis registered in Community Health Centers of Rancaekek, Linggar and Nanjung Mekar in Bandung, Indonesia. A total sampling was used with a total number of 52 patients. Data on knowledge, attitude, and practice were measured via validated questionnaires and observation sheets. Frequency distribution, mean and median were used for data analysis. Results: Of the total respondents, 65.4% of the respondents had good knowledge about cough etiquette (median value 83.33 and IQR 20), 50.9% had negative cough etiquette attitude (mean value 47.87 and SD 5.885), and 63.5% had bad practice in cough etiquette (median value 5 and IQR 2). Conclusions: The result of this study is expected to be an input for primary health care facilities in doing improvement in delivering health education to patients with tuberculosis and their families about the good and right cough etiquette, which focus on the affective and psychomotor aspects to prevent the spread of tuberculosis and decrease its infection. This article has been corrected. A separate erratum can be seen at https://doi.org/10.33546/bnj.1153